2022
DOI: 10.1186/s10020-022-00504-6
|View full text |Cite
|
Sign up to set email alerts
|

The novel transcriptomic signature of angiogenesis predicts clinical outcome, tumor microenvironment and treatment response for prostate adenocarcinoma

Abstract: Angiogenesis plays the critical roles in promoting tumor progression, aggressiveness, and metastasis. Although few studies have revealed some angiogenesis-related genes (ARGs) could serve as prognosis-related biomarkers for the prostate cancer (PCa), the integrated role of ARGs has not been systematically studied. The RNA-sequencing data and clinical information of prostate adenocarcinoma (PRAD) were downloaded from The Cancer Genome Atlas (TCGA) as discovery dataset. Twenty-three ARGs in total were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In model construction, univariate proportional hazards model (Cox) analysis was performed to screen out the survival-related lncRNAs with ‘survival’ R package ( 20 ). Then, least absolute shrinkage and selection operator (LASSO) regression with tenfold cross-validation was employed to minimize the errors for the construction of an ideal risk model ( 21 ). The risk score calculation formula was the sum of coefficient × x (x is the FPKM value of each cuproptosis-related lncRNA) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…In model construction, univariate proportional hazards model (Cox) analysis was performed to screen out the survival-related lncRNAs with ‘survival’ R package ( 20 ). Then, least absolute shrinkage and selection operator (LASSO) regression with tenfold cross-validation was employed to minimize the errors for the construction of an ideal risk model ( 21 ). The risk score calculation formula was the sum of coefficient × x (x is the FPKM value of each cuproptosis-related lncRNA) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent year, algorithms have been developed to predict tumor purity using gene expression data based on the TCGA database. For example, (36,37), breast cancer (38,39), colorectal cancer (40)(41)(42) and hepatocellular carcinoma (43), which demonstrated that such big-data-based algorithms are effective, although its utility on immune and/or stromal scores in glioblastoma multiforme (GBM) has not been explored in detail.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Recent evidence suggests that PRAD prognosis is heavily dependent on the tumor microenvironment [ 4 ]. The tumor immune microenvironment (TIME), comprised of extracellular matrix, stromal cells, and other tumor associated cells, can modulate the tumor’s response to therapy and can influence the progression of the tumor [ 5 ]. TIME has been reported to profoundly influence the growth and metastasis of cancer.…”
Section: Introductionmentioning
confidence: 99%